Blind interference suppression for MC-CDMA system with transmit diversity - HU Bing; LI Ping-an; YU Bian-zhang (Tongxin xuebao)
Blind interference suppression for multicarrier CDMA （MC-CDMA） system was investigated, in which space-time block coding based transmit diversity was used. It was considered that the fading coefficients corresponding to subcarriers were discrete Fourier transform of multipath coefficients. By investigating the code space in frequency domain and the data vector space of the multipath signals, the noise-subspace-based approach was used to perform blind channel estimation. To suppress multiuser access interference （MAI）, a projection-based auxiliary vector （PAV） algorithm was proposed. The algorithm has low computation complexity. It can provide efficient interference suppression with low input signal-to-interference-and-noise ratio （SINR）, and shows robust performance with high input SINR.